2017
DOI: 10.1016/j.cbpa.2016.09.026
|View full text |Cite
|
Sign up to set email alerts
|

The Greenland shark: A new challenge for the oxidative stress theory of ageing?

Abstract: 21The free radical theory of ageing predicts that long-lived species should be more 22 resistant to oxidative damage than short-lived species. Although many studies support 23 this theory, recent studies found notable exceptions that challenge the generality of this 24 theory. In this study, we have analysed the oxidative status of the Greenland shark 25 (Somniosus microcephalus), which has recently been found as the longest living 26 vertebrate animal known to science with a lifespan of at least 272 years. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…However, long-lived species from the genus Ceratitis, such as C. cosyra and C. scaevolae, did not have outstanding TAC in comparison with the other species with shorter lifespans. This aligns with findings in vertebrates where exceptional lifespan is not associated with exceptional antioxidant protection [16][17][18] . Nevertheless, average lifespan significantly increased with TAC, and this was not due to the phylogenetic relationship between species.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, long-lived species from the genus Ceratitis, such as C. cosyra and C. scaevolae, did not have outstanding TAC in comparison with the other species with shorter lifespans. This aligns with findings in vertebrates where exceptional lifespan is not associated with exceptional antioxidant protection [16][17][18] . Nevertheless, average lifespan significantly increased with TAC, and this was not due to the phylogenetic relationship between species.…”
Section: Discussionsupporting
confidence: 90%
“…These assumptions are often supported at a sex-specific level, with the longer-lived sex often having lower oxidative damage 14,15 . However, some exceptions have been found in very long-lived species which have neither high antioxidant protection nor low oxidative damage [16][17][18] . While a number of comparative studies support the FRTA, experimental work has generated equivocal results.…”
mentioning
confidence: 99%
“…Comparative analysis with other species showed that these sharks display high values of GPx in muscles and low levels of carbonylated proteins in erythrocytes, suggesting a beneficial proportion of redox parameters. At the same time, oxidative status was not correlated with longevity, which is instead a form of adaptation to specific environmental conditions [123]. Despite the fascinating value of the Greenland shark's lifespan, neither cellular nor molecular determinants of this phenomenon have been identified.…”
Section: The Mystery Of Greenland Shark Longevitymentioning
confidence: 96%
“…When differences in markers of oxidative stress were compared in mollusc species with a six-fold difference in life span, Gruber et al (50) reported correlations between DNA oxidation and biological, but not chronological age, implying that nucleic acid oxidation reflected intrinsic ageing mechanisms. On the other hand, since surrogate markers of oxidative damage in red blood cells and muscle did not correlate to lifespan in Greenland sharks, the free radical theory of ageing may not apply to all long-lived species (51). In the case of the Greenland shark, oxidative status may rather be shaped to the life in cold and deep artic water (51).…”
Section: Free Radical and Mitochondrial Theories Of Ageingmentioning
confidence: 99%
“…On the other hand, since surrogate markers of oxidative damage in red blood cells and muscle did not correlate to lifespan in Greenland sharks, the free radical theory of ageing may not apply to all long-lived species (51). In the case of the Greenland shark, oxidative status may rather be shaped to the life in cold and deep artic water (51).…”
Section: Free Radical and Mitochondrial Theories Of Ageingmentioning
confidence: 99%